2017
DOI: 10.1016/j.quaint.2015.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Lagomorph predation represented in a middle Palaeolithic level of the Navalmaíllo Rock Shelter site (Pinilla del Valle, Spain), as inferred via a new use of classical taphonomic criteria

Abstract: a b s t r a c tLagomorph remains at Pleistocene sites may accumulate through the action of hominins, raptors or carnivores. Actualistic studies have described reliable taphonomic indicators that allow human and nonhuman involvement in such accumulations to be distinguished. However, discriminating between possible animal predators is not easy, because the prey remnants they leave may undergo the same kinds of taphonomic transformation. The main aim of the present work was to identify the agent, human or non-hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 36 publications
0
8
0
4
Order By: Relevance
“…The Ap Horizon is Holocene. A different version of this lithostratigraphic sequence was published by Arriaza et al (2017), but it contains several errors that are corrected in this work: the TL samples are incorrectly located and the legend of the injected sediment (Layer D) should be the same than the lower layer (Layer F), as explained above.…”
Section: Contextmentioning
confidence: 99%
“…The Ap Horizon is Holocene. A different version of this lithostratigraphic sequence was published by Arriaza et al (2017), but it contains several errors that are corrected in this work: the TL samples are incorrectly located and the legend of the injected sediment (Layer D) should be the same than the lower layer (Layer F), as explained above.…”
Section: Contextmentioning
confidence: 99%
“…Rodriguez-Hidalgo et al (2015) studied undigested rabbit remains fed by a female lynx to her cubs in denning season, finding the aforementioned taphonomic signals as well as small scores and pits produced by the teeth of infant lynxes. Arriaza et al (2015) found similar modifications in the middle Palaeolithic level of the Navalmaíllo Rock Shelter (Pinilla del Valle, Spain), and Rosado-Méndez et al (2015) in the Aurignacian levels of Terrasses de la Riera dels Canyars (Gavà, Barcelona, Spain).…”
Section: Introductionmentioning
confidence: 75%
“…Arriaza et al . () found similar modifications in the middle Palaeolithic level of the Navalmaíllo Rock Shelter (Pinilla del Valle, Spain), and Rosado‐Méndez et al . () in the Aurignacian levels of Terrasses de la Riera dels Canyars (Gavà, Barcelona, Spain).…”
Section: Introductionmentioning
confidence: 99%
“…Así, para confi rmar que las concreciones son fragmentos coprolitos, su composición química debe corresponder a la de los huesos (fosfato cálcico y carbonato cálcico). Los mamíferos carnívoros producen pasta de hueso durante el proceso de digestión, a diferencia de las aves rapaces, que no lo hacen (Arriaza et al, 2017). La identifi cación de pasta de hueso sobre los restos óseos o dentarios implica que dichos restos proceden de la disgregación de excrementos de carnívoros y no de egagrópilas de aves.…”
Section: Identifi Cación De Fragmentos De Coprolitosunclassified